A driving simulator study to evaluate the effects of different types of median separation on driving behavior on 2 + 1 roads. (February 2023) - Calvi, Alessandro; Cafiso, Salvatore Damiano; D'Agostino, Carmelo; Kieć, Mariusz; Petrucci, Gianmarco
Highlights: The operational and safety benefits of 2+1 roads are investigated. The driving simulator study tested different types of median separation. Driving performance have been collected and compared among the different median separators. Driving speeds are not affected by the type of median separations, while lateral positions are. 2+1 roads increase traffic operations and reduce the average delays. Abstract: In recent years, several countries have started to introduce 2 + 1 roads into their road networks. Although some studies have recognized the great benefits of using 2 + 1 roads, few studies have investigated the effects of different design features of 2 + 1 roads on driver behavior and driving performance, including the type of median separation between opposing traffic flows. The overall aim of this driving simulator study is to determine whether different types of median separation on 2 + 1 roads affect driving behavior, and to provide new insights for designing more effective and safer 2 + 1 roads. A driving simulator study was carried out, and forty-six participants took part in the experiments. The scenario exactly reproduced an existing two-lane rural road in Poland where 2 + 1 sections are implemented; four different median separation types were tested: 1) double-line markings only; 2) reflective elements; 3) flexible guideposts; 4) cable barriers. The effects of the different types of median separation on driving behavior were statistically analyzed using data from 184 simulation tests. The results of the study suggest that the type of median separation significantly affects driving behavior on 2 + 1 roads. While the driving speeds on the passing lane did not differ significantly between the four configurations of the median separation, the lateral position of the passing vehicle on the additional lane was found to be significantly influenced by the type of separation, with a greater distance from the median recorded when the cable barriers were implemented. The potential of using driving simulation to test different solutions for 2 + 1 roads and select the most effective alternative in terms of safety and operation is demonstrated in this study. The results of this study can also be used to improve the behavioral models that can be implemented in the traffic micro-simulation of 2 + 1 road conditions.